Cell sorting for parallel lithium-ion battery systems: Evaluation based on an electric circuit model. (May 2016) - An, Fuqiang; Huang, Jun; Wang, Chengyu; Li, Zhe; Zhang, Jianbo; Wang, Sean; Li, Ping
Graphical abstract: Highlights: Separate current tracking of each cell in a parallel block. A practical electric circuit model for parallel blocks. Comparisons and suggestions of methods for parametrizing the model. Statistical evaluation of cell sorting strategies over battery lifetime. Demonstration of importance of an aging descriptor in cell sorting. Abstract: This study dwells upon two key aspects of cell sorting including what descriptors should be concerned and how stringent the limits of these descriptors should be. Evaluation is made on a parallel multi-cell block using an electric circuit modelling (ECM) approach, which features a model validation based on separate current tracking of each cell in the parallel cell block via Hall sensors, and a detailed comparison of methods to determine model parameters. We find that: (1) the ECM can accurately capture the current balancing behavior in the parallel block; (2) the current interrupt method with a rest duration of 120 s is recommended for the determination of cell resistance; (3) the current distribution in the parallel block is insensitive to the hysteresis in open circuit voltage (OCV); (4) cell-to-cell variations decrease the capacity of the block (5) a descriptor accounting for aging variations among cells is suggested to be included in the cell sorting process and the OCV drop rate can be a potential candidate.